The first discovery of fossil rhopalids (Heteroptera: Coreoidea) from Middle Jurassic of Inner Mongolia, China - Yao, Yunzhi; Cai, Wanzhi; Ren, Dong (Zootaxa, 2006)
Two new genera and two new species of fossil rhopalid, Miracorizus punctatus gen. & sp. nov. and Longiclavula calvata gen. & sp. nov., are described and illustrated. They were collected from the Middle Jurassic Jiulongshan Formation of Inner Mongolia, China. This is the earliest fossil record of the family Rhopalidae in the world.